The Effect of Waiting Room Service Quality and Departure Terminal Facilities on Passenger Satisfaction in International Airport Kualanamu North Sumatra - Hidayat, Novrizal; Tanjung, Ali Mukti; Karim, Ahmad; Ichsan, Reza Nurul; Hidayat, Ferry (International Journal of Economics (IJEC), 2024)
This study aims to identify, analyze, and assess the effect of waiting room service quality and departure terminal facilities on passenger satisfaction at Kualanamu International Airport, North Sumatra. This study uses a quantitative approach with associative methods. A total of 100 respondents were selected through random sampling techniques and data were collected using questionnaire instruments that include variables of waiting room service quality, departure terminal facilities, and passenger satisfaction. Data analysis was done by multiple linear regression techniques. The results of partial analysis showed that the quality of Service waiting room has a significant effect on passenger satisfaction with the value of tcount= 6.311 which is greater than Ttable=1.660 and significance of 0.000 (<0.05). Similarly, the departure terminal facilities have a significant effect with the value of t count=4.127 which is also greater than T table=1.660 and significance 0.000 (<0.05). Simultaneously, the quality of Service waiting room and departure terminal facilities significantly affect passenger satisfaction with a value of Fcount=152.284 greater than Ftable=3.09 and significance 0.000 (<0.05). Determination value of 75.3% indicates that the variable quality of service lounge and departure terminal facilities explain most of the variations in passenger satisfaction variables. This study recommends that Kualanamu airport managers improve service quality by adding seats, improving air conditioning systems and renewing entertainment facilities. Further research, it is recommended to expand the scope of variables, use qualitative methods and conduct comparisons between airports in order to broaden the outlook and develop a more comprehensive service improvement strategy.